Comparative Analysis: Value at Risk (VaR) with Parametric Method, Monte Carlo Simulation, and Historical Simulation of Mining Companies in Indonesia - Darmawan, Muhammad Rizky; Widyono, Fathi Atha Putra (Research Collaboration Community (RCC), 2024)
This study aims to conduct a comparative analysis between three Value at Risk (VaR) calculation methods, namely the Parametric (Variance-Covariance) method, Monte Carlo Simulation, and Historical Simulation, in measuring market risk in mining companies in Indonesia. The mining industry in Indonesia faces the risk of high commodity price volatility, thus requiring an appropriate approach in measuring potential financial losses. This study uses historical stock data from several major mining companies in Indonesia to analyse the difference in results between the three VaR methods. This study found that the smallest VaR value is owned by PTBA company. Along with the level of stability shows that PTBA company is more stable than other companies. This is inversely proportional to the TINS company which has a large VaR value and high volatility.